A low power wideband varactorless VCO using tunable active inductor - Omar Faruqe; Rumana Akhter; Md Tawfiq Amin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents a wideband varactorless voltage controlled oscillator (VCO) based on tunable active inductor in 90 nm CMOS process which yields a tuning range of 1.22 GHz to 3.7 GHz having a tuning scope of 100.5%. The designed VCO can be used for wideband wireless applications. The proposed VCO consumes a very low power (1.05 ~ 2.5) mW with the change of tuning voltages (0.3 ~ 0.9) V and provides a differential output power of (1.17 ~ -5.13) dBm. The VCO exhibits phase noise of -80.50 dBc/Hz@2.74 GHz and the Figure of Merit (FOM) is -147.73 dBc/Hz @2.74 GHz at 1MHz offset frequency. Achievement of high tuning range by altering the inductance of inductor which paves the way for eliminating the MOS varactor that recedes the overall silicon area consumption, is the noteworthy outcome of the proposed VCO. Furthermore, considering the dc power consumption, figure of merit (FOM) and consistency of performance parameters over tuning range, the proposed VCO outstrips the other referred VCOs.